1996
DOI: 10.1097/00006534-199604001-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Magnetic Resonance Angiography prior to Pharyngeal Flap Surgery in Patients with Velocardiofacial Syndrome

Abstract: Twenty consecutive patients with velocardiofacial syndrome underwent magnetic resonance angiography (MRA) to determine if abnormalities of the neck arteries would contraindicate pharyngeal flap surgery. All 20 patients were found to have anomalies to the carotid arteries, vertebral arteries, medially placed internal carotids, low carotid bifurcations, and tortuous or kinked internal carotids. The internal carotids were found to be almost directly under the mucous membrane of the pharynx in two patients. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1
5

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 13 publications
2
81
1
5
Order By: Relevance
“…It has also been found that there is a high frequency of palatal and pharyngeal asymmetry in VCFS that can also only be determined by endoscopic assessment [Chegar et al, 2006]. Among the anomalies seen in the pharynx are major vascular anomalies including abnormal placement of the internal carotid arteries [MacKenzie-Stepner et al, 1987;Mitnick et al, 1996;Tatum et al, 2002] and tortuous or kinked vertebral arteries [Mitnick et al, 1996]. These vascular anomalies have been cited as potentially dangerous risks when pharyngeal surgery is being planned [MacKenzie-Stepner et al, 1987;Mitnick et al, 1996;Tatum et al, 2002].…”
Section: Clinical Features and The Vcfs Phenotypementioning
confidence: 99%
See 3 more Smart Citations
“…It has also been found that there is a high frequency of palatal and pharyngeal asymmetry in VCFS that can also only be determined by endoscopic assessment [Chegar et al, 2006]. Among the anomalies seen in the pharynx are major vascular anomalies including abnormal placement of the internal carotid arteries [MacKenzie-Stepner et al, 1987;Mitnick et al, 1996;Tatum et al, 2002] and tortuous or kinked vertebral arteries [Mitnick et al, 1996]. These vascular anomalies have been cited as potentially dangerous risks when pharyngeal surgery is being planned [MacKenzie-Stepner et al, 1987;Mitnick et al, 1996;Tatum et al, 2002].…”
Section: Clinical Features and The Vcfs Phenotypementioning
confidence: 99%
“…Among the anomalies seen in the pharynx are major vascular anomalies including abnormal placement of the internal carotid arteries [MacKenzie-Stepner et al, 1987;Mitnick et al, 1996;Tatum et al, 2002] and tortuous or kinked vertebral arteries [Mitnick et al, 1996]. These vascular anomalies have been cited as potentially dangerous risks when pharyngeal surgery is being planned [MacKenzie-Stepner et al, 1987;Mitnick et al, 1996;Tatum et al, 2002]. It has also been reported that the muscle tissue in the pharynx has abnormally small fiber size and abnormal distribution of fiber type [Zim et al, 2003].…”
Section: Clinical Features and The Vcfs Phenotypementioning
confidence: 99%
See 2 more Smart Citations
“…Because of reported skull and vertebral abnormalities (Arvystas and Shprintzen 1984;Beemer et al 1986;Finkelstein et al 1993;Ming et al 1997;Ryan et al 1997), the skull base structures were assessed. In addition, cerebral and cervical arteries were also assessed using magnetic resonance angiography (MRA) because of a reported high prevalence of carotid and vertebral arterial anomalies in 22qDS (Goldberg et al 1993;MacKenzie-Stepner et al 1986;Mitnick et al 1996).…”
Section: Introductionmentioning
confidence: 99%